ANALYSIS OF DETERMINING PRIORITY OF ROAD MAINTENANCE PROGRAM IN THE REGION OF KEDIRI ROAD AND BRIDGE MANAGEMENT DEPARTMENT OF HIGHWAYS EAST JAVA PROVINCE USING MULTI CRITERIA ANALYSIS (MCA) METHOD - Haniffan Daruquthni Baihaqi; Catur Arif Prastyanto (Institut Teknologi Sepuluh Nopember (ITS), 2023)
Road conditions are vital for smooth land transportation to supporting the economy. Good road management programs, funded by the government through road administrators, are necessary for achieving steady road conditions. The Provincial Government of East Java through the Department of Public Works of Highways has an important role in the process of handling provincial roads. Budget limitations, both Regular APBD funds and special allocation funds and other funds, create a distinct challenge for road administrators in determining an effective and optimal road management program. Based on previous research studies, priority determination of road handling can be carried out using Multi Criteria Analysis. Priority determination criteria used in this study are technical criteria which include: existing traffic conditions, road stability conditions, degree of saturation, travel speed, and travel time; financial and economic criteria which include: Vehicle Operational Costs, Time Value, Benefit Cost Ratio, and Net Present Value. In this study it will be seen based on the results of prioritized maintenance handling found at Link 176 Kediri - Blitar City Boundary for average daily traffic technical criteria has a difference in value of 3,190 cur/hour, with an average road condition of 27.12%, difference in degree of saturation of 0.346, the difference in travel speed is 3.409 km/hour, the difference in travel time is 3.661 minutes and for economic criteria vehicle operational costs has a difference in value of Rp. 8,662,656,168, the difference in the Benefit Cost Ratio is 0.60 and the difference in the Net Present Value is -Rp. 8,382,143,904.